PORNOGRAFI: ANTARA KEPEMILIKAN DAN DOMINASI TUBUH - ., Mukalam (Islamic University of Indonesia, 2006)
Pornography denotes the controversial issue. The controversies happen because of the issue in the unclear cut position, for instance, the problem of definition. The definition of pornography is not so easy either in term of ethymology or terminology. In other words there is no an agreement regarding its definition. It also involves the other dimensions, for example political dimension, that of morality, religion, law, social, esthetic, and gender. In this sense, it emerges controversies in term of how to mean the gender equality. The question is what the meaning of gender equality? Does pornography happens because of inequality or conversely? Kata kunci: pronogarfi, ketidaksetaraan, gender, dan feminisme